Why MREL won't help much - Tobias Tröger (Goethe University Frankfurt, Institute for Monetary and Financial Stability (IMFS), 2017)
The bail-in tool as implemented in the European bank resolution framework suffers from severe shortcomings. To some extent, the regulatory framework can remedy the impediments to the desirable incentive effect of private sector involvement (PSI) that emanate from a lack of predictability of outcomes, if it compels banks to issue a sufficiently sized minimum of high-quality, easy to bail-in (subordinated) liabilities. Yet, even the limited improvements any prescription of bail-in capital can offer for PSI's operational effectiveness seem compromised in important respects. The main problem, echoing the general concerns voiced against the European bail-in regime, is that the specifications for minimum requirements for own funds and eligible liabilities (MREL) are also highly detailed and discretionary and thus alleviate the predicament of investors in bail-in debt, at best, only insufficiently. Quite importantly, given the character of typical MREL instruments as non-runnable long-term debt, even if investors are able to gauge the relevant risk of PSI in a bank's failure correctly at the time of purchase, subsequent adjustment of MREL-prescriptions by competent or resolution authorities potentially change the risk profile of the pertinent instruments. Therefore, original pricing decisions may prove inadequate and so may market discipline that follows from them. The pending European legislation aims at an implementation of the already complex specifications of the Financial Stability Board (FSB) for Total Loss Absorbing Capacity (TLAC) by very detailed and case specific amendments to both the regulatory capital and the resolution regime with an exorbitant emphasis on proportionality and technical fine-tuning. What gets lost in this approach, however, is the key policy objective of enhanced market discipline through predictable PSI: it is hardly conceivable that the pricing of MREL-instruments reflects an accurate risk-assessment of investors because of the many discretionary choices a multitude of agencies are supposed to make and revisit in the administration of the new regime. To prove this conclusion, this chapter looks in more detail at the regulatory objectives of the BRRD's prescriptions for MREL and their implementation in the prospectively amended European supervisory and resolution framework.
urn:nbn:de:hebis:30:3-438820
Keywords: G01; G18; G21; G28; K22; K23; 330; MREL; TLAC; G-SIB; bail-in; bank resolution